2003
DOI: 10.1590/s0021-75572003000800012
|View full text |Cite
|
Sign up to set email alerts
|

Analgesia e sedação em situações de emergência e unidades de tratamento intensivo pediátrico

Abstract: Objective: To review the current strategies for use of sedatives and analgesics in emergency rooms and intensive care units. Sources of data:Original data from our emergency rooms and intensive care units; Medline literature review focused on sedatives and analgesic drugs; textbooks. Summary of the findings:Despite the advances in understanding pain in children, in many critical care units the misguided treatment of pain and anxiety still results in significant morbidity. Difficulties in communication, invasiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
3
0
5
Order By: Relevance
“…15,[23][24][25] Set against this there appears to be a certain reluctance to use drugs because of the pharmacokinetic and metabolic alterations that commonly occur after the third trimester of pregnancy and last until at least 6 months of age, making the definition of dosages and the safety of drugs less predictable. 26,27 A systematic review of nine neonatology studies concluded that while there is not sufficient evidence to prove the safety of the use of pre-intubation drugs with newborns, their use should be considered. 11 The wide variation in drugs chosen and doses given reflects the lack of training in airway management both on medical undergraduate courses and at the start of postgraduation.…”
Section: Discussionmentioning
confidence: 99%
“…15,[23][24][25] Set against this there appears to be a certain reluctance to use drugs because of the pharmacokinetic and metabolic alterations that commonly occur after the third trimester of pregnancy and last until at least 6 months of age, making the definition of dosages and the safety of drugs less predictable. 26,27 A systematic review of nine neonatology studies concluded that while there is not sufficient evidence to prove the safety of the use of pre-intubation drugs with newborns, their use should be considered. 11 The wide variation in drugs chosen and doses given reflects the lack of training in airway management both on medical undergraduate courses and at the start of postgraduation.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, os efeitos benéficos da sedação e analgesia sobre a pressão intracraniana, risco de dano à via aérea, redução do tempo do procedimento de intubação e conforto do paciente deveriam ser considerados 15,[23][24][25] . Por outro lado, parece existir certo receio ao uso de drogas devido às alterações farmacocinéticas e de metabolismo que costumam ocorrer a partir do terceiro trimestre de gestação e persistir pelo menos até os 6 meses de vida, tornando a definição das doses e a segurança dos fármacos mais imprevisíveis 26,27 . Revisão sistemática realizada com nove estudos em neonatologia concluiu que, apesar de não existirem dados suficientes para estabelecer a segurança do uso de medicações pré-intubação em neonatos, deve-se considerar seu uso 11 .…”
Section: Discussionunclassified
“…(16,(34)(35)(36)(37)(38) The following drugs are more frequently used in neonatal intensive care units. (9,39) Non-opioid analgesics Among the drugs in this group only paracetamol is released for use in the neonatal period, however, in Brazil, it is not produced for parenteral use, restricting utilization in neonatal intensive care units. (16,40) The recommended dose is 10 to 15 mg/kg for full-term newborn and 10 mg/kg for premature, every six hours.…”
Section: Knowledge About Drugs Available and Adverse Effectsmentioning
confidence: 99%